# How do you solve #4x - 3 = 11x - 73#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 4x - 3 = 11x - 73, you would first combine like terms by subtracting 4x from both sides, which gives you -3 = 7x - 73. Then, you would add 73 to both sides to isolate the variable term, resulting in 70 = 7x. Finally, you would divide both sides by 7 to solve for x, giving you x = 10.

By signing up, you agree to our Terms of Service and Privacy Policy

- Wildhorse Co, accepted a national credit card for a $10600 purchase, The cost of the goods sold is $6600, The credit card company charges a 5% fee. What is the impact of this transaction on net operating income?
- How do you solve # 6x = 36#?
- How do you solve #(18-x)/-9=-5#?
- How do you solve #9w-4(w-2)=3(w+1)-9#?
- How do you solve for x in #a(x + b) = c#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7